THE ROLE OF THE FAMILY IN RECOGNIZING AND HANDLING IMPACT OF POST STROKE DEPRESSION IN THE WORK AREA SRONDOL HEALTH CENTER, SEMARANG CITY - Ahmad Riadi (Wealth Community Empowerment, 2025)
Stroke is the number one cause of disability and the number three cause of death in the world after heart disease and cancer, in both developed and developing countries. This community service activity is to provide education to families regarding post-stroke depression; how to recognize and treat the effects of post-stroke depression independently at home. Implementation of community service activities in an effort to reduce the incidence of post-stroke depression by increasing family knowledge in recognizing and treating the impact of post-stroke depression at home with implementation and evaluation preparation stages with a target number of 30 people who have family or relatives who have suffered a stroke. This community service activity was carried out well and achieved the aim of the activity, namely increasing family knowledge regarding how to recognize and treat the impact of post-stroke depression. The family plays an important role in recognizing the symptoms of depression that appear after a stroke, as well as providing the necessary emotional and physical support. Through good communication and understanding of the patient's condition, families can help speed up recovery and improve quality of life. Apart from that, collaboration with health workers is very necessary to provide appropriate interventions and support patients' mental health. Thus, the active role of the family is very influential in overcoming the negative impacts of post-stroke depression